The Early Bird Gets the Worm: How Early Morning Exercise Creates Inspired Learners and Educators (LEARNing Landscapes, 2012)
As the nation grapples with how to shrink the achievement gap and raise the level of achievement for all students, educators need to rethink how they deliver instruction and how students learn. Sitting in chairs all day long is not the most conducive way to learn. It is critical that schools look towards morning movement and exercise programs to stimulate increased brain activity and energize children to be ready and able to focus on their academics throughout the day.
Keywords: exercise; brain activity; morning movement; instruction; informal learning